Quantitative characterization of volume of cavities in hydrodynamic cavitation device using computational fluid dynamics - Poleto, Cristiano (2020)
Hydrodynamic cavitation has been extensively studied for its potential to remove emerging pollutants. Despite the advance of the experimental studies involving this phenomenon, computational studies that evaluate the influence of the geometry of the cavitation devices on the flow parameters are still necessary. The purpose of this article was to evaluate the influence of the change in the geometry of a Venturi device on the volume of cavities formed in its divergent section using Computational Fluid Dynamics (CFD). The geometric parameters modified in the Venturi were: the diffuser angle and the relation between the height and the width of the throat (h/w). The volume of cavities is an important parameter because it influences the cavitation intensity. A cavitational bench system was constructed in order to obtain input data for simulation. The results showed that the increase in the diffuser angle from 6.5° to 18.5° gradually reduced the volume of cavities from 93 mm3to 10 mm3. Between the relations h/w = 0.05 and h/w = 0.45 was observed the formation of cavities between 106 mm3 and 77 mm3, however between h/w = 0.45 and h/w = 1.0 there was the formation of 213 mm3. Therefore, Venturi’s with diffuser angle less than 6.5º and relation h/w greater than 0.45 produce greater volume of cavities. The greater volume of cavities will not necessarily produce greater cavitational intensity, since cavitation clouds can be formed and reduce the implosion intensity of the cavitation bubbles.